2013
DOI: 10.1007/s00436-013-3276-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy of an Imidacloprid 10 % / Flumethrin 4.5 % Polymer Matrix Collar (Seresto®, Bayer) against the Australian Paralysis Tick (Ixodes holocyclus) in Dogs

Abstract: Two placebo-controlled pen studies were conducted to assess the efficacy of an imidacloprid 10 %/flumethrin 4.5 % polymer matrix collar (Seresto ® , Bayer; Investigational Veterinary Product (IVP)) against the Australian paralysis tick (Ixodes holocyclus). Dogs assigned to the placebo (n = 8) or IVP (n ≥ 8) groups had collars (placebo or IVP) attached on Day 0 and were infested with 30 unfed, adult, female I. holocyclus at 14-28 day intervals over 227 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The European Food Safety Authority reserves its rights, view and position as regards the issues addressed and the conclusions reached in the present document, without prejudice to the rights of the authors. (Bos and Curtis, 2002) An efficacy of 0.95 against I. ricinus for deltamethrin 4% was reached over a period of 5.5 months Imidacloprid EC 428-040-8 (Smith et al, 2013) Substance is very toxic to aquatic life, is very toxic to aquatic life with long lasting effects and is harmful if swallowed.…”
Section: Disclaimermentioning
confidence: 99%
See 1 more Smart Citation
“…The European Food Safety Authority reserves its rights, view and position as regards the issues addressed and the conclusions reached in the present document, without prejudice to the rights of the authors. (Bos and Curtis, 2002) An efficacy of 0.95 against I. ricinus for deltamethrin 4% was reached over a period of 5.5 months Imidacloprid EC 428-040-8 (Smith et al, 2013) Substance is very toxic to aquatic life, is very toxic to aquatic life with long lasting effects and is harmful if swallowed.…”
Section: Disclaimermentioning
confidence: 99%
“…External usecollar/ear tag A combination of imidacloprid 10% /flumethrin 4.5% reached a maximum efficacy against I. holocyclus of 1 87 post-treatment before decreasing to 0.66 227 days posttreatment (Epe et al, 2003) External usetopic/spray A combination of Imidacloprid 10%/Permethrin 50% had an efficacy of 0.92 37 days post treatment (Hellmann et al, 2003) A combination of Imidacloprid 10%/Permethrin 50% had an efficacy of 0.96 28 days post treatment Flumethrin (Smith et al, 2013) External usecollar/ear tag A combination of imidacloprid 10% /flumethrin 4.5% reached a maximum efficacy against I. holocyclus of 1 87 post-treatment before decreasing to 0.66 227 days posttreatment Metaflumizone EC 604-167-6 (Hellmann et al, 2007) Substance is very toxic to aquatic life, is very toxic to aquatic life with long lasting effects and may cause damage to organs through prolonged or repeated exposure.…”
Section: Disclaimermentioning
confidence: 99%
“…Smith et al (2013) demonstrated 4 month efficacy (> 97.9 %) for the Seresto ® collar against the I. holocyclus. However, repellency was not assessed in this study.…”
Section: Dantasmentioning
confidence: 99%
“…It has been shown to achieve long-term persistent efficacy of 8 months against fleas (Ctenocephalides felis felis) (Stanneck et al 2012b(Stanneck et al , 2012c) and 4 months against I. holocyclus on dogs (Smith et al 2013). The Seresto ® collar has also been shown to be highly effective in the prevention of trans mission of VBD from ticks to dogs (Dantas-Torres et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The collar also exhibits repellent (anti feeding) efficacy and has the potential to prevent infections with flea and tick transmitted agents Fourie et al 2013a;Fourie et al 2013b;Lappin et al 2013;Otranto et al 2013, Reichard et al 2013Brianti et al 2014). The collar contains two actives, the insecticide imidacloprid active against fleas and lice, and the acaricide flumethrin active against ticks and mites (Stanneck et al 2012b;Stanneck et al 2012c;Brianti et al 2013;Smith et al 2013). The actives themselves have a relatively long history.…”
Section: Introductionmentioning
confidence: 99%